IMPROVING STUDENTS' ENGLISH LANGUAGE SKILLS THROUGH THE ENGLISH MATRICULATION PROGRAM AT THE UPT LANGUAGE DEVELOPMENT CENTER UIN RADEN INTAN BANDAR LAMPUNG - Fini Widya Fransiska; Bayu Grendo Sigarete (Jurnal Pengabdian Masyarakat, 2024)
English language skills are an urgent need for students in the era of globalization to support academic and career success. However, the limited English language skills of new students at UIN Raden Intan Bandar Lampung are a challenge that requires a strategic solution. The English matriculation program implemented at the UPT Language Development Center aims to improve students' English language competence through an active learning approach. This activity involves a pre-test, practice-based learning, and a post-test to evaluate the effectiveness of the program. The results of the activity showed a significant increase in students' English language skills, with an average increase in post-test scores of 20–30 points. These findings emphasize the importance of the matriculation program as a systematic effort to support students' academic and professional preparation and recommend the development of similar programs to be implemented in other universities.